On the wrong track - Hockensmith, Steve (Hockensmith, Steve. Holmes on the range., 2007)
Sherlock Holmes-worshiping cowpokes Big Red and Old Red Amlingmeyer are back in another Old West adventure. This time they sign on as guards for the hated Southern Pacific Railroad<U+2014>and quickly find themselves heading full-steam toward disaster! They<U+2019>ve barely left the station when the train they<U+2019>re on is robbed and the baggage man loses his head...literally. Also on board for the wild ride: a drunken Pinkerton, a mysterious beauty, a secretive Chinese doctor and a deadly swamp adder with a taste for cowboys. Will Big Red and Old Red make it to the end of the line alive? Not if the bad guys get their way!